Study on Structure and Properties of Jackfruit Gum and Epoxidized Jackfruit Gum - Nguyen, Thu Ha; Tran, Ngoc Anh; Tran, Thi Thuy; Phan, Trung Nghia; Tran, Van Anh (Old Journal, 2020)
Jackfruit gum and epoxidized jackfruit gum may be used as model compounds for the characterization of structure and properties of liquid natural rubber and liquid epoxidized natural rubber. Jackfruit gum was extracted from trunk, green fruit and ripen fruit and purified in order to obtain cis-1,4-polyisoprene, followed by epoxidation with fresh peracetic acid. The characterization of structure and properties of the materials were carried out through NMR, FTIR, viscosity measurement and nitrogen determination. The result shows that jackfruit gum extracted from trunk and green fruit are quite similar in structure and properties, whereas that extracted from ripen fruit contains the highest nitrogen content and molecular weight. The investigation of epoxidation of jackfruit gum shows that epoxy group is successfully introduced to jackfruit gum.